Os museus e os outros : uma etnografia das classificações, alteridades e agenciamentos no Museu Rondon de Etnologia e Arqueologia da UFMT - Souza, Ryanddre Sampaio de (2016)
This dissertation aims to analyze the formation process of the museological collection of the Rondon Museum of Ethnology and Archaeology of the Federal University of Mato Grosso, in order to rethink museums in contemporaneity as instances crossed by several agencies, spaces that express desires, tensions and emotions, beyond the simple act of collecting. To this end, we attempted to bring forth an anthropological reflection by analyzing the process of assemblage and classification of the cultural heritage musealized in this space, understanding these objects as bearers of relations and cosmologies, in order to comprehend the ways in which this collection was built and which perspectives conducted these practices and the production of discourses on alterity. We consider here the archives and museum collections as legitimate ethnographic fields, taking into account their social and symbolic contexts, since such inventories are composed, fueled and maintained by people, social groups and institutions, as a result of procedures of building and organizing knowledge. Through the delineation of the relationship between Anthropology and museums, using the history of the discipline as support, we intent to relativize the characterization of museums and their discursive practices in contemporary time. I propose other perspectives to a new multivocal dialogue between the ethnographic museums, the indigenous peoples and the use of their collections, such as highlighting the actions that produced perspectives about the difference or indigenous peoples there represented.